Account of Temperature Change at Calibration of Air Flow Sensor - A. Kryukov, Yu.; A. Mikheev, M; Ð•. Golovchenko, T; V. Ivanov, V; K. Lytkin, L (International Journal of Engineering and Technology, 2018)
The article describes of temperature change consideration during the calibration of air flow sensor for a car engine. The sensor uses a blade made of elastic material with strain gauges applied to the front and the back surfaces, the deformation of which is measured and recalculated into a mass flow of air. They suggested the system of equations whose solution makes it possible to determine the mass flow rate and air temperature according to the known signal values at the measuring bridge output and the measuring circuit resistance. The coefficients of equation system are determined during calibration and then are recorded into the memory of the microcontroller sensor.Â Â